A coprodução internacional na indústria cinematográfica - Rolla, Gustavo Ferreira (2024)
This dissertation addresses the Brazilian film industry from an economic perspective with the aim of analyzing the effect of international co-production on the commercial performance of films in the Brazilian exhibition market from 2005 to 2022. Although Brazil has significantly expanded its production capacity, capturing larger market shares remains a significant challenge for strengthening the national film industry. Thus, this work aims to provide contributions towards overcoming this bottleneck. The theoretical frameworks guiding the research view the film industry in its economic and productive dimensions, recognizing it as an important component of the creative economy. They also analyze the dynamics of international co-production as a means of strengthening the industry. To achieve the presented objective, the research adopted a quantitative approach, through which we gathered secondary data on the audience of Brazilian films shown in theaters, available from the Brazilian Cinema and Audiovisual Observatory (OCA) of the National Film Agency (ANCINE). These data were first analyzed using descriptive statistical techniques, followed by linear regression analysis. The research hypothesis that Brazilian films produced with international co-production perform better commercially in the domestic market than Brazilian films without international co-production was not confirmed. We believe there are other possible advantages of conducting international co-productions, related to learning dynamics, resource sharing, and access to international markets, which warrant further study. However, within the scope of this dissertation, we identified that Brazilian films without international co-production achieved the same commercial performance in the domestic market as films produced with international co-production. The work has applicability in contributing to the proposal of better public policies related to strengthening the Brazilian film industry.